First comparative proteomic and in vitro behavioral study of Echinococcus granulosus metacestodes in Felis catus - Maglioco, Andrea; Miana, Vanesa V.; Valacco, María Pía; Agüero, Facundo A.; Gertiser, María Laura; Avila, Héctor G.; Barbery Venturi, Melisa S.; Jensen, Oscar; Juárez Valdez, Alejandra Y.; Prieto González, Elio A.; Fuchs, Alicia G. (Frontiers in Veterinary Science, 2025)
Echinococcus granulosus sl is the etiological agent of cystic echinococcosis affecting livestock and humans worldwide. Felis catus contributes to the dispersion of parasite eggs and the connection between wild and domestic populations. The potential larval development in the intermediate host or its capacity to develop the worm stage in the definitive host is not disclosed. Protein expression profiles may reveal parasite adaptations to the intermediate host. This study presents, for the first time, a comparative analysis of the in vitro behavior, cytogenetics, and Liquid Chromatography-mass/mass spectrometry (LC-MS/MS)-based molecular profile of two Echinococcus granulosus s.s. (G1 genotype) metacestodes isolated from two naturally infected, unrelated Felis catus hosts without FIV. Protein abundance index (emPAI) analysis showed distinct proteomic signatures. Metacestode from Cat # 1 was predominantly characterized by proteins involved in glucose intermediary metabolism, energy production, Adenosin- tri- phosphate (ATP)-dependent contractile filaments, antigenic proteins, and DNA repair, suggesting a molecular profile potentially more adapted to survival or development within the definitive host. In contrast, metacestode from Cat # 2 predominantly expressed proteins associated with inflammation and membrane components rich in heparan sulfate, suggesting reduced viability or invasiveness. Despite similarities in in vitro parameters, including cytogenetics, primary parasite cell growth, and protoscolex development, mass spectrometry analysis revealed differences in protein expression patterns between the two metacestodes. In conclusion, this study highlights molecular markers that may contribute to understanding the adaptive strategies and pathogenic potential of E. granulosus s.s. metacestodes. Host diversity and parasite metabolic profile may provide new insights into parasite behavior, virulence, and host–parasite interactions.